The Effectiveness of Inclusive School Programs on Access and Equity of Educational Services in Sidoarjo Regency - Mashuri Mashuri; Eny Haryati; Widyawati Widyawati (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This research is motivated by the significance of inclusive education as a way to guarantee access and equity for students with special needs in Sidoarjo Regency. Even with robust national policies advocating for inclusive schools, their impact at the regional level is still not thoroughly examined. This study aims to assess the impact of inclusive school initiatives on enhancing educational access and equity of services. The aims are to (1) evaluate the access rates of students with special needs to both formal and non-formal education; (2) analyze equity of services in relation to facilities, teaching standards, and learning results; (3) pinpoint factors that facilitate and hinder implementation; and (4) develop policy suggestions for enhancing equitable services. The research utilizes a mixed-methods strategy incorporating a sequential explanatory framework that integrates quantitative survey information from 30 schools along with qualitative interviews conducted with policymakers, educators, and parents. The results show that the success of inclusive programs in Sidoarjo is intermediate, with significant differences between urban and rural schools. Leadership, teacher effectiveness, and collaboration across sectors stand out as crucial factors for success. The research indicates that maintaining inclusive education necessitates regional policy coordination, development of human resources, and data-driven monitoring to guarantee equity and equal learning chances for every student